Asylum and immigration cooperation after Lisbon: New competencies, better policy? - Steffen Angenendt; Roderick Parkes (Stiftung Wissenschaft und Politik (SWP), 2009)
The juncture is propitious to predict upcoming changes in European asylum and migration policy. After all, the institutional alterations being introduced by the Lisbon Treaty are predicated upon a desire to increase the European Union's capacity for action in home affairs. And the Stockholm Programme prescribes the strategic use of this institutional architecture over the next five years. Or at least, it ought to. In actual fact, the as yet unpublished Programme is unlikely to provide much in the way of far-sighted programming in asylum and immigration policy - and Lisbon's institutional changes may actually complicate decision-taking. Together they are a recipe for the persistence of the current deficits in policymaking, rather than for change
Keywords: 320